Immune mediated inflammatory diseases: moving from targeted biologic therapy, stem cell therapy to targeted cell therapy - Liang, Zhenguo; Xie, Hui; Wu, Dongze (Frontiers in Immunology, 2025)
Despite the advancements in targeted biologic therapy for immune-mediated inflammatory diseases (IMIDs), significant challenges persist, including challenges in drug maintenance, primary and secondary non-responses, and adverse effects. Recent data have strengthened the evidence supporting stem cell therapy as an experimental salvage therapy into a standard treatment option. Recent preclinical and clinical studies suggested that chimeric antigen receptor T cell (CAR-T) therapy, which depleting tissue and bone marrow B cells, may lead to improvement, even inducing long-lasting remissions for patients with IMIDs. In this review, we address the unmet needs of targeted biologic therapy, delineate the critical differences between stem cell transplantation and CAR-T therapy, evaluate the current status of CAR-T therapy for IMIDs and explore its potential and existing limitations.